A CARE-compliant case report: Lung transplantation for a Chinese young man with idiopathic pleuroparenchymal fibroelastosis. Issue 19 (May 2017) - Huang, Hui; Feng, Ruie; Li, Shan; Wu, Bo; Xu, Kai; Xu, Zuojun; Chen, Jingyu
Abstract: Rational: Pleuroparenchymal fibroelastosis (PPFE) is a rare interstitial lung disease that is characterized radiologically by apical pleural thickening and histologically by elastic fibrosis of the visceral pleura. Although PPFE cases have been reported occasionally since this disease was initially described, most such cases have involved secondary PPFE. Idiopathic PPFE (iPPFE) cases have been less thoroughly studied. There are no effective medications for patients with iPPFE. Patient Concerns: A 34-year-old man with no asbestos or cigarette exposure was admitted to our ward due to worsening cough and exertional dyspnea for 10 years. He had a "flattened thoracic cage" and bibasilar inspiratory crackles without finger clubbing. A series of chest computed tomography scans during the preceding 10 years revealed the presence of gradual, exaggerated, upper lung–predominant, diffuse pleural thickening and dense subpleural opacification with traction bronchiectasis. Diagnosis: He was performed with video-assisted thoracic surgical (VATS) lung biopsy. The pulmonary histopathologic examination showed thickened visceral pleura and prominent subpleural fibroelastosis, confirming the diagnosis of iPPFE. Intervention: After the failure of treatment with prednisone plus cyclophosphamide and sequential pirfenidone administration, he was arranged with bilateral lung transplantation two years later. Outcomes: The patient did not require supplemental oxygenation anymore after he recovered from lung transplantation. Lessons: Bilateral lung transplantation might be tried for the end-stage iPPFE cases.